A 60-year-old lady with leonine facies: A rare diagnosis - Deepti Mutreja; Abhishek Purohit; Pawan K Singh; H P Pati (Wolters Kluwer Medknow Publications, 2012)
Systemic mastocytosis is a rare clonal disorder characterized by mast cell infiltration of one or more organs, with or without skin involvement. Leonine facies is a rare presentation and corresponds to the morphologic manifestation of diffuse dermal infiltration of the face as a result of long standing disease. Bone marrow aspiration and biopsy findings in a 60-year-old woman, who had extensive cutaneous infiltration due to systemic mastocytosis, resulting in 'leonine facies,' are described, and causes of leonine facies are discussed.